Slavery in Enlightenment America – Crèvecoeur’s bilingual approach - Still, Judith (Liverpool University Press, 2018)
Crèvecoeur’s reception has been skewed by a focus on his writing in English. His work on slavery has been neglected - with the exception of one extract on a bestial Southern atrocity, and even that letter has been undermined as an anti-slavery text. In fact, he wrote significant abolitionist pieces as well as engaging in abolitionist activism. However, his writing can be ambiguous when he describes kindly-treated slaves in the Northern provinces. On the one hand, this seems to detract from the abolitionist case, but, on the other hand, relative to much contemporary writing, humanizes black Americans as part of the community with common practices, feelings and rational aims. The cosiness of this black and white family-community is, however, shadowed in Crèvecoeur’s texts by (a) the antithetical figure of the Native American who starkly formulates the absolute value of liberty – as against trading some freedom for comfort, wealth or even survival, and (b) the parallel with domestic animals.